Impression Cytology in the Evaluation of Ocular Surface Squamous Neoplasia- A Retrospective Cohort Study National - Meghana Patil; TS Nagaraj; Mohan Kulkarni (National Journal of Laboratory Medicine, 2023)
Introduction: Ocular Surface Squamous Neoplasia (OSSN) are a diverse group of lesions varying from Conjunctival Intraepithelial Neoplasia (CIN) to invasive Squamous Cell Carcinomas (SCC). Histopathological examination is the gold standard technique in diagnosing them. However, it is invasive and may not be suitable in recurrent cases. Numerous minimally invasive techniques are available to diagnose OSSN cytologically. This study employs Impression Cytology (IC) to diagnose ocular squamous neoplastic lesions and compare it with the histological diagnosis. Aim: To utilise IC in the diagnosis of OSSN and to compare its findings with histopathological diagnosis. Materials and Methods: This was a retrospective cohort study, conducted in a Tertiary Eye care Hospital, Hubli, Karnataka, India during January 2023. The data included was over a period of three years (from July 2016 to June 2019). A total of 44 eyes (34 patients), in which both biopsy and IC done, were included. The patients’ age, sex and ocular examination findings were recorded. The cytological and histopathological slides were retrieved from the archives and examined morphologically. The cytological findings were compared with histopathological diagnosis and the sensitivity and specificity of the IC technique were calculated. The data was analysed using Microsoft excel sheets. Results: A total of 34 patients were studied ranging from 19 to 85 years. The mean age was 49 years, 21 (61.76%) of them were males and 13 (38.24%) were females. In 24 patients, single eye was affected and in 10 patients bilateral eye involvement was seen. Histology revealed that there were 18 (40.90%) CIN I cases, 4 (9.09%) CIN II, 5 (11.36%) CIN III and 17 (38.65%) SCC. On cytology, 3 (6.82 %) were normal conjunctival epithelium, 30 (68.18 %) were dysplasia and 11 (25.00 %) were SCC. On cyto-histomorphological analysis, 35 (79.55 %) were concordant, out of 44 diagnosis. IC has a sensitivity of 88.89% and specificity of 64.71% to detect dysplasia. To diagnose SCC, it has sensitivity of 64.71% and 100% specificity. Conclusion: According to the present study observations, IC is an excellent preliminary tool to investigate suspected neoplastic lesions of ocular surface. It has a very good concordance with histopathological diagnosis. IC is highly sensitive to detect dysplasia (CIN) and is very specific to diagnose SCC.